2012
DOI: 10.1111/j.1464-410x.2012.11371.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgical margin status on prostate‐cancer‐specific mortality

Abstract: OBJECTIVE To examine the relative impact of a positive surgical margin (PSM) and other clinicopathological variables on prostate-cancer-specific mortality (PCSM) in a large retrospective cohort of patients undergoing radical prostatectomy (RP). PATIENTS AND METHODS Between 1982 and 2011, 4569 men underwent RP performed by a single surgeon. Of the patient population, 4461 (97.6%) met all the inclusion criteria. The median (range) age was 58 (33–75) years and the median prostate-specific antigen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
3
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 31 publications
1
56
3
2
Order By: Relevance
“…After the multivariate regression analysis, positive surgical margin was the independent factor with greatest impact on BCR (3.4 OR, 1.97-5.99 CI 95%). This fact coincides with the results of most of the work in the literature [20][21][22][23]. A higher OR value does occur in our case, but it is likely to be due to our analysis involving high and very high-risk tumors.…”
Section: Discussionsupporting
confidence: 92%
“…After the multivariate regression analysis, positive surgical margin was the independent factor with greatest impact on BCR (3.4 OR, 1.97-5.99 CI 95%). This fact coincides with the results of most of the work in the literature [20][21][22][23]. A higher OR value does occur in our case, but it is likely to be due to our analysis involving high and very high-risk tumors.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the NCCN high-risk group and a Gleason score at surgery ≥8 were identified as the risk factors for BCR (Table 4). Several reports support these results, indicating that the advanced pathological features are likely to increase the risk of BCR for the patients with RM1 (5,6,22,23). Here, we ultimately focused on the uPSA value measured early after prostatectomy because a value >0.02 ng/ml was the most potent risk factor for disease recurrence (HR 13.10) compared with NCCN high-risk group (HR 2.05) and Gleason score ≥8 (HR 2.47).…”
Section: Discussionmentioning
confidence: 60%
“…Wright et al reported in a study that the mortality risk due to prostate cancer was 1.7 times higher in patients with PCM than those without it (22). Chalfie et al suggested the adverse effect of PCM on survival in their study (23), but they also noted that this effect was relatively low when compared to Gleason score and pathological stage.…”
Section: Discussionmentioning
confidence: 98%